2007
DOI: 10.1111/j.1600-0420.2007.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic inclusion cysts of the iris: a longterm prospective case series

Abstract: . Purpose:  Post‐traumatic cysts of the iris pose a diagnostic and therapeutic challenge for ophthalmic surgeons. This prospective case series highlights the clinical spectrum and longterm outcomes of different modes of treatment in these cases. Methods:  Eleven cases of post‐traumatic iris inclusion cysts, treated with Nd:YAG laser and/or surgical excision were evaluated prospectively over periods ranging from 6 months to 3 years. Ultrasound biomicroscopy features and postoperative outcomes in each were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 9 publications
0
33
0
4
Order By: Relevance
“…8 Our case had a good surgical outcome, even after 6 months post surgery there were no complication or recurrence, probably as the cyst was removed completely. In our case, the cilia might have entered into the AC along with corneal, conjunctival or eyelid epidermis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…8 Our case had a good surgical outcome, even after 6 months post surgery there were no complication or recurrence, probably as the cyst was removed completely. In our case, the cilia might have entered into the AC along with corneal, conjunctival or eyelid epidermis.…”
Section: Discussionmentioning
confidence: 80%
“…The time taken between trauma and appearance of the cyst may range from 6 months to 20 years. 8 In a review of cystic iris lesions in children, only 4 of 57 iris cysts were of secondary origin, of which two were post-traumatic epithelial ingrowth cysts. 9 Small iris cysts may remain asymptomatic and static in size.…”
Section: Discussionmentioning
confidence: 99%
“…As many studies have found, surgical intervention has better outcome and lower recurrence rate compared to laser therapy [2,4,5]. Other non-invasive technique include irrigation with 100% ethanol and subsequent excision of the epithelial implantation cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatments had been advocated including Nd: YAG laser puncture of cyst, cyst aspiration, surgical removal by cystectomy or total excision with iridocyclectomy and laser treatment with photocoagulation or cryotherapy [1,2,4,5]. As many studies have found, surgical intervention has better outcome and lower recurrence rate compared to laser therapy [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation